Ethical Issues in Indigenous Archaeology: Problems with Difference and Collaboration - González-Ruibal, Alfredo (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2019)
The critique of archaeology made from an indigenous and postcolonial perspective has been largely accepted, at least in theory, in many settler colonies, from Canada to New Zealand. In this paper, I would like to expand such critique in two ways: on the one hand, I will point out some issues that have been left unresolved; on the other hand, I will address indigenous and colonial experiences that are different from British settler colonies, which have massively shaped our understanding of indigeneity and the relationship of archaeology to it. I am particularly concerned with two key problems: alterity – how archaeologists conceptualize difference – and collaboration – how archaeologists imagine their relationship with people from a different cultural background. My reflections are based on my personal experiences working with communities in southern Europe, Sub-Saharan Africa and South America that differ markedly from those usually discussed by indigenous archaeologies.